Participatory planning and village tourism SMEs: a case study of Bantul Regency, Yogyakarta, Indonesia - Erlis Saputra; Erda Rindrasih (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Tourism, with its multiplier effect, is believed to be a savior for developing countries to better their economic conditions. It is also central to the development of peripheral, remote and insular regions by facilitating transitions from agriculture-based economies to service industries. Community participation approaches have long been advocated as essential for sustainable tourism development. In Indonesia village based small and medium enterprises in the tourism industry are on the rise with significant numbers of villages developing as tourist destinations. The attractions of these destinations are their natural beauty, industrial products and cultural values and artifacts. This development raises the question of government intervention in the planning process of such village based, SMEs. This paper analyses village based tourism SMEs in the Bantul Regency, Indonesia with special reference to the background of the SMEs development, its effect on the local community, and the nature of the government’s role or intervention in the planning process. The data were gathered through library research, government’s document investigations, observations, and several interviews with stakeholders and entrepreneurs. It was found that the village-based tourism SMEs faced several challenges including the lack of tourism industry knowledge and education, and the lack of capital and promotional ideas to start their businesses.